Opinion of pupils in the upbringing process in school. (Journal of Educational Sciences, 2016)
The article presents the analysis of the public opinion poll pupils of 7-11 classes of secondary schools of the city Almaty. The survey was obtained data about the General perceptions of school and school life; different aspects of educational activities in the school; social well-being of schoolchildren of Almaty; value orientation of schoolchildren; медиапредпочтения school children; the problem of students and ways of their solution; discipline and education of legal consciousness of pupils; the evaluation of labour and future professional guidance of pupils. In the framework of the research was used квотная multi-stage random sample in proportion to the number of students in senior grades of General education day schools in the areas of the city.
Keywords: education; the school; the areas of educational activity